Suicide, taedium uitae et droit romain sous le Principat - François Waquet (Criminocorpus)
Suicide was viewed in various ways by the Ancients. For the Stoics, it was the conclusion of reasoning rather than the outcome of a violent emotion. In this regard, several historical studies had already highlighted the patrimonial reasons underlying certain suicides at the beginning of the Roman Empire. Extending this perspective, but with a strictly legal approach, this article explores the category of taedium vitae, "disgust with life," as a legitimate cause of suicide in Roman law.